New Moneys under the New Normal? Bitcoin and Gold Interdependence during COVID Times - Pablo Agnese; Jonathan Thoss (Institute of Labor Economics (IZA), 2021)
Bitcoin in particular and so-called cryptocurrencies in general have shaken up the financial world and seem to be claiming an increasing size of the market share. These new virtual assets present investors with significant opportunities, but also with significant risks. This paper analyzes the connection between one such crypto, bitcoin, and other traditional assets (e.g. metals) in times of financial turbulence. Our impulse-response function and variance decomposition analyses indicate that, as of late, bitcoin has become increasingly interdependent with gold, and seems just as suitable to hedge against market uncertainty—we believe this is a very timely conclusion given the pervasive uncertainty that dominates post-pandemic life.
Keywords: G15; G12; G11; 330; bitcoin; gold; COVID-19; impulse response